2021
DOI: 10.21053/ceo.2019.01921
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Inhalant Allergens in South Korea: A Computational Model of Allergic Sensitization

Abstract: Objectives. Sensitization to specific inhalant allergens is a major risk factor for the development of atopic diseases, which impose a major socioeconomic burden and significantly diminish quality of life. However, patterns of inhalant allergic sensitization have yet to be precisely described. Therefore, to enhance the understanding of aeroallergens, we performed a cluster analysis of inhalant allergic sensitization using a computational model. Methods. Skin prick data were collected from 7,504 individuals. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Cluster analysis is exploratory in nature and there are several different clustering algorithms to choose from. We selected Ward’s method of hierarchical clustering as it has been used in other studies assessing allergen clusters in different populations [ 62 ]. Agglomerative hierarchical clustering includes all observations into a cluster and even though three clusters were optimally selected, there are likely smaller, but important, sub clusters within the main clusters [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis is exploratory in nature and there are several different clustering algorithms to choose from. We selected Ward’s method of hierarchical clustering as it has been used in other studies assessing allergen clusters in different populations [ 62 ]. Agglomerative hierarchical clustering includes all observations into a cluster and even though three clusters were optimally selected, there are likely smaller, but important, sub clusters within the main clusters [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on the status of aeroallergen sensitization in Koreans [9][10][11][12][13][14][15][16][17][18][19][20]. However, many of these studies are old, and it is difficult to consider them representative of the national situation as only a limited number of aeroallergens were investigated, or relatively few patients were enrolled at a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, hierarchical cluster analysis identified seven clusters: plants (grass, tree, weed, and peanut), dust mites (Dermatophagoides farina, Dermatophagoides pteronyssinus), pets (dog/cat), cockroach/shrimp, molds (Alternaria alternata, Aspergillus fumigatus), foods (egg white/cow's milk), and rodents (mouse/rat). In another study, medical records of 4,360 patients with multiple allergen simultaneous test results at a dermatology clinic in South Korea were retrospectively reviewed and a cluster analysis was performed to elucidate the allergen-specific IgE cluster pattern [5]. In total, 39 items were grouped into eight clusters and each cluster had characteristic features.…”
mentioning
confidence: 99%
“…In the current issue of Clinical and Experimental Otorhino-laryngology, Kim et al [5] investigated patterns of sensitization to inhalant allergens through a computational analysis using a four-parameter unified Richards model to identify the clustering of inhalant allergic sensitization. In total, 7,504 individuals' skin prick data were collected and analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation